META ANALYSIS OF STRATEGIES AND UTILIZATION OF ELECTRONIC JOURNALS FOR GRADUATE STUDENT UNIVERSITY OF STATE MALANG IN EFFORTS PRODUCE INTERNATIONALLY REPUTED SCIENTIFIC PUBLICATIONS - Ansor, Sokhibul; Setyosari, Punaji; Degeng, I Nyoman Sudana; Waras, Waras (Universitas Pendidikan Indonesia, 2019)
Scientific publications in journals of international repute act as a medium for self-actualization academics in the development of science internationally. Higher education institutions that have the quality of education, science, and technology are good tend to have a high number of international publications. To produce scientific publications of high qualityÂ must be supported by research and a source of reference quality. In an effort to improve the scientific publication of national repute academic environment. Malang State University. providing electronic information resources in the form of an electronic journal that comes from a variety of electronic information resources, in the hope utilized by students in an effort to increase scientific publication of international repute. The effort is also supported by a set of rules that requires that academic graduate students have a scientific publication of international repute as a graduation requirement